PENGEMBANGAN PARIWISATA BERBASIS MASYARAKAT DI DESA TUA PEJAT KECAMATAN SIPORA UTARA KABUPATEN KEPULAUAN MENTAWAI - Yenni Jufri; Naufal Raid; Donna Ikranova F; Mernawati Mernawati (Jurnal Public Administration, Business and Rural Development Planning, 2019)
Tourism is a source of income that can be continually updated and rejuvenated, this form of rejuvenation of tourist areas can be in the form of renovations, and regular maintenance, therefore tourism is an important investment in the non-oil and gas sector for Indonesia. Tourism which is a future economic investment will automatically facilitate the circulation of goods and services in tourist attractions. Furthermore tourism will enhance national economic stability, but of course the success in tourism development as above will be felt if the supporting factors are well prepared. Tourism potential that is high in the Mentawai Islands Regency region should be optimized, not only seen as a potential regional income, but as an effort to preserve regional culture that has begun to be abandoned. As one of the main motivators of industrial development, tourism in the Mentawai Islands district government needs a good role to manage and market tourism products so that they can become a potential source of income for the region. Through various policy breakthroughs, it is expected that regional governments will be able to embrace various stakeholders for the sustainability of a competitive and sustainable tourism industry based on community empowerment.